Aging: the experience of nurses working in a hospital - Maria de Lourdes Dias Braz; Beatriz Aparecida Ozello Gutierrez; Glaucia Martins de Oliveira Alvarenga; Jeane Roza Quintans; Aparecida Bernardes dos Santos; Rosa Yuka Sato Chubaci (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to understand the experience of aging in the perspective of nurses working in a hospital environment. Methods: descriptive study with a qualitative approach, with interviews based on six guiding questions analyzed through Martín Heidegger's perspective on Phenomenology. Results: eleven nurses with a mean age of 46.2 years old participated in the study. The study unveiled the phenomenon of being a nurse in the process of aging. The speeches were divided into three categories: Being-there and the different faces of aging; Being-in-the-world of work; Being-in-the-world of old age. Final Considerations: there was a trend towards a positive search for aging and active old age, but aspects such as fear of loneliness and abandonment ("Being-in-the-world of old age") emerged through fearful speeches. There is a need for gerontological education so that nurses can properly discuss and plan a healthy aging process and achieve a dignified old age.